Temporal trends in mortality and causes of death in patients with incident atrial fibrillation: a nationwide register study from 2010 to 2018 - Kouki, Elis; Salmela, Birgitta; Aro, Aapo; Halminen, Olli; Teppo, Konsta; Haukka, Jari; Putaala, Jukka; Linna, Mika; Mustonen, Pirjo; Hartikainen, Juha; Airaksinen; Juhani K E; et al. (BMJ Publishing Group, 2025)
OBJECTIVES: Atrial fibrillation (AF) is associated with increased mortality. Previous studies have reported conflicting results in temporal trends of mortality after AF diagnosis. We aim to address this disparity by investigating the 1-year mortality and causes of death in Finnish patients diagnosed with AF between 2010 and 2017.
DESIGN: The Finnish AntiCoagulation in Atrial Fibrillation (FinACAF) study is a nationwide retrospective register-based cohort study.
SETTING: The FinACAF study has gathered information on all Finnish AF patients between 2004 and 2018, with information from all national healthcare registers and data from all levels of care (primary, secondary and tertiary care).
PARTICIPANTS: We included patients with an incident AF diagnosis (International Classification of Diseases, 10th Revision code I48) between 2010 and 2017. To ensure a cohort of only incident AF, we excluded patients who used any oral anticoagulant during the year before cohort entry as well as patients with a recorded use of warfarin between 2004 and 2006. Patients under 20 years of age were excluded, and patients with permanent migration abroad before 1 January 2019 were excluded, N=157 658.
PRIMARY OUTCOME MEASURES: 1-year all-cause, cardiovascular (CV) and cause-specific mortality following AF diagnosis.
RESULTS: The study cohort consisted of 157 658 incident AF cases (50.1% male, mean age 72.9 years). Both all-cause and CV mortality declined from cohort entry years 2010-2017 (from 12.9% to 10.6%, mortality rate ratio (MRR) 0.77; 95% CI 0.73 to 0.82 in cohort entry year 2017 with 2010 as reference; and from 7.4% to 5.2%, MRR 0.68; 95% CI 0.63 to 0.74, respectively). Overall mortality and CV mortality were lower in women than in men throughout the study period (MRR 0.66; 95% CI 0.63 to 0.69 and MRR 0.53; 95% CI 0.50 to 0.56, respectively). Deaths attributable to ischaemic heart disease decreased during the study period (from 30.7% to 21.6%, MRR 0.51; 95% CI 0.49 to 0.62 in 2017 vs 2010), whereas dementia and Alzheimer's disease increased as a cause of death over time (6.2% to 9.9%, MRR 1.19; 95% CI 0.96 to 1.48 in 2017 vs 2010). The CHA2DS2-VASc score associated strongly with 1-year survival (p<0.0001).
CONCLUSIONS: Our study reiterates that mortality after diagnosis of AF has decreased. The CHA2DS2-VASc score highlights the need to treat comorbidities as it strongly associates with patient 1-year survival after initial AF diagnosis.